KONFLIK ANTAR UMAT TERHADAP KEYAKINAN BERGAMA DI INDONESIA - Muhammad Nazaruddin (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2017)
Religion is a kind of social system created by its adherents who process on the non empirical powers it believes and empowers to achieve their salvation. Every religion always carries a mission of peace and harmony of life, not just between people, But also among fellow creatures of God. But in the historical level the religious mission is not always articulate. Besides as a social unifier tool, religion becomes an element of conflict that can give to loss of life and property. Conflict is a squabble; Disagreements; Contradiction. If this word is combined with social terms it becomes a disagreement between members of society who are comprehensive in life. According to conflict theory, society is a state of continuous conflict between groups and classes and tends towards disputes, tensions, and changes. The conflict between Muslims and Christians if analyzed further, is not entirely due to the different conceptions between the two adherents. Political, social, economic, and so on are often detached from observation, so religion is used as a means of legitimizing the aggressive and radical attitudes of the group to one another.